The Effectiveness of Legal Protection Against Bullying in the Medical Residents' Education - Nancy S. Lampus; Ibnu Subarkah; M. C. Inge Hartini (Locus: Jurnal Konsep Ilmu Hukum, 2026)
The increasing prevalence of bullying during medical residents’ education has tarnished the integrity of education in Indonesia, harmed various parties, and reduced public trust in the specialist doctor education system. The government has enacted several regulations as efforts to prevent and address bullying in specialist doctor education, accompanied by the imposition of strict sanctions on perpetrators. This study aims to analyze the effectiveness of statutory regulations in providing legal protection to trainees during the Medical Residents’ Education Program (PPDS-1). The research employs an empirical legal research method with a sociological-empirical approach. The types and sources of data include primary data collected through interviews and secondary data obtained from the literature. The analysis applies qualitative descriptive techniques, with explanations presented in a structured and systematic manner. Conclusions are drawn to address the core issues under investigation. Normatively, the substance of the regulations is sufficiently clear and relatively appropriate; however, gaps remain in their implementation, as they have not yet achieved optimal effectiveness.